Oral administration of Shiga toxin-producing Eschericcia coli induces intestinal and systemic specific immune response in mice - Fernández Brando, Romina Jimena (2014)
Hemolytic uremic syndrome (HUS) is the major complication of gastrointestinal infections with enterohemorrhagic Escherichia coli (EHEC) and is mediated by the production of Shiga toxins (Stx). Although it has been previously reported that not only HUS patients but healthy children have anti-Stx antibodies, very little is known about how these infections impact on mucosal immune system to generate a specific immune response. This work aimed to evaluate the immune responses elicited after a single oral dose of EHEC in a mouse model of HUS at weaning. We found sequential activation of T and B lymphocytes together with an increased percentage of IgA-bearing B cells in Peyer´s patches and mesenteric lymph nodes. We also found fecal anti-EHEC IgA and serum anti-Stx2 IgG in EHEC-inoculated mice. Besides, these mice were partially protected against an intravenous challenge with Stx2. These data demonstrate that one episode of EHEC infection is enough to induce activation in the gut-associated lymphoid tissue, especially the B cell compartment, and lead to the production of specific IgA in mucosal tissue and the generation of systemic protection against Stx2 in a percentage of intragastrically inoculated mice. These data also support the epidemiologic observation that a second episode of HUS is very rare.